PENGEMBANGAN MODEL AKREDITASI SEKOLAH TINGKAT SLTP DAN SMU - SUMARNO SUMARNO; NUR KHOLIS (Universitas Negeri Yogyakarta, 2002)
Abstract This study was aimed to developing school accreditation odel, covering the aspects of organization, working scheme, instrumentation, scoring system, and the determination of the accreditation standing. The instrument has been restricted to the essential elements so that schools can be expected to be able to evaluate themselves. It has been tried out at three Junior and three Senior High Schools in each of two provinces, the Province of Yogyakarta and the Provinces of Lampung. Those schools are the schools of high, medium, and low standing. The accreditation organization resulted consists of three levels, namely the School Accreditation Board, the Regional Accreditation Board, and the National accreditation Board. Keywords: accreditation model, school accreditation board, regional accreditation board, and national accreditation board.